The Development Design of Group Counseling With Behavioral Contract Technique To Reduce Students’ Academic Procrastination Behavior - Alfiani Fernita Sari; Yulia Ayriza (Edunesia: Jurnal Ilmiah Pendidikan, 2021)
Abstract: There are varoius techniques in the counseling approach which are implemented according to the counselee's problem. One of the popular counseling techniques in the behavioral approach is called the behavioral contract. The purpose of this study was to develop a group counseling stage design of the behavioral contract technique to solve the student's academic procrastination problem. Development of the group counseling stage design of the behavioral contract technique used the Borg and Gall development model. The development of the design consist of three stages which begins with the need asessment stage, the product development planning stage, and the initial product development stage. The data collection technique was conducted by interviewing 5 counseling teachers from different schools. Product validation was carried out with expert counseling expert judgment with 3 revisions. The result was the design of the behavioral contract technique group counseling stage can be applied in counseling service in schools that was consisting of 3 stages, namely: the beginning stage, the working stage, and the terminating stage. Each stage of the group counseling contains activity steps that should be done. Design of group counseling with behavioral contract technique is compiled for 8 meetings with a duration of 45 minutes per meeting. This research is only up to the third stages, namely developing the initial product. Therefore, the next step in this research will be further developed and published in another article. Abstrak: Teknik dalam pendekatan konseling sangat bermacam-macam yang dapat digunakan sesuai dengan masalah konseli. Salah satu  teknik konseling dalam pendekatan behavior yaitu teknik behavioral contract. Tujuan penelitian ini adalah mengembangkan rancangan tahapan konseling kelompok teknik behavioral contract untuk mengatasi masalah prokrastinasi akademik siswa. Pengembangan rancangan konseling kelompok  teknik behavioral contract menggunakan model pengembangan Borg and Gall. Pengembangan produk rancangan ini terdiri dari 3 tahapan, diawali dari tahap asesmen kebutuhan, tahap perencanaan mengembangkan produk, dan tahap mengembangkan produk awal. Teknik pengumpulan data dilakukan dengan wawancara kepada 5 orang guru bimbingan konseling yang berbeda sekolah. Validasi produk dilakukan dengan expert judgement ahli konseling sebanyak 3 kali revisi. Hasilnya adalah rancangan tahapan konseling kelompok dengan teknik behavioral contract dapat diaplikasikan dalam layanan konseling di sekolah yang terdiri dari 3 stage/tahap, yaitu: beginning stage, working stage, dan terminating stage. Setiap tahapan konseling kelompok terdapat langkah-langkah kegiatan yang harus diselesaikan. Rancangan tahapan konseling kelompok teknik behavioral contract disusun untuk 8 pertemuan dengan durasi watu 45 menit setiap pertemuan. Penelitian ini hanya sampai tahap ketiga yaitu mengembangkan produk awal. Oleh karena itu langkah berikutnya pada penelitian ini akan dikembangkan lebih lanjut dan dipublikasikan pada artikel lain.